REGENERASI PERAKARAN PLANTLET IN VITRO DAN EX VITRO PADA KULTUR JARINGAN CENDANA (Santalum album) - Asri Insiana Putri; Toni Herawan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Cendana (Santalum album Linn.) is one of the important hemiparasite species due to its high value essential oil for pharmaceutical industries. However, since1998 this species has been categorized as vulnerable by the IUCN Red List. The propagation of cendana has been hampered by inadequacy in regeneration, either through sexual or vegetative propagation. Regeneration of cendana through in vitro technique is still limited due to the difficulty in rooting and acclimatization. The purpose of this study is to observe the effect of clones, in vitro and ex vitro techniques on the primary and secondary root development. Two clones of cendana: Clone A.III.4.14 and WS28 were tested in Gresshoff & Doy culture media enriched by IBA 20 mg/l; IAA 0.15 mg/l and kinetin 0.15 mg/l. Root development was observed for six months of culture for in vitro and three months after acclimatization in a greenhouse for ex vitro. The results of this study showed that Clone A.III.4.14 formed primary root in lower percentage rate (41.85%) than Clones WS28 (60,44%), on the contrary it grew secondary root in higher percentage rate (58.15%) than Clone WS28 (39,56%). The ex vitro following the acclimatization showed that the root hairs grew only in the plantlets which formed secondary root during in vitro. This result indicates an important of clone’s selection for secondary root development during in vitro to obtain a better root system in the success of acclimatization of cendana.